Osteoporosis and diabetes - M. Barbagallo; G. Zagone; E. Quarta; M. Muratore; L.J. Dominguez (PAGEPress Publications, 2011)
Diabetes mellitus and osteoporosis are chronic diseases with an elevated and growing incidence in the elderly. Recent epidemiological studies have demonstrated an elevated risk of hip, humerus and foot fractures in elder diabetic subjects. While type 1 diabetes is generally associated with a mild reduction in bone mineral density (BMD), type 2 diabetes, more prevalent in old subjects, is frequently linked to a normal or high BMD. Studies on experimental models of diabetes have suggested an altered bone structure that may help to explain the elevated risk of fractures observed in these animals and may as well help to explain the paradox of an incremented risk of fractures in type 2 diabetic elderly in the presence of normal or elevated BMD. In addition, diabetic elderly have an increased risk of falls, consequent at least in part to a poor vision, peripheral neuropathy, and weaken muscular performance. Diabetes may affect bone tissue by different mechanisms including obesity, hyperinsulinemia, deposit of advanced glycosilation end products in collagen fibre, reduced circulating levels of IGF-1, hypercalciuria, renal function impairment, microangiopathy and chronic inflammation. A better understanding of these mechanisms may help implement the prevention of fractures in the growing population of mature diabetics.